Synthesis and Evaluation of the Biological Profile of Novel Analogues of Nucleosides and of Potential Mimetics of Sugar Phosphates and Nucleotides - Xavier, Nuno M.; Lucas, Susana D.; Jorda, Radek; Schwarz, Stefan; Loesche, Anne; Csuk, René; Oliveira, M. Conceição (Synlett, 2015)
The synthesis of purine/triazole 6'-isonucleosides and of glucuronic acid/glucuronamide-derived N-glycosylsulfonohydrazides through efficient and stereo- or regioselective methodologies is described. Their structures were envisaged to mimic nucleosides, sugar phosphates, or nucleotides, and were expected to provide potential inhibitors of therapeutically relevant enzymes, the active sites of which could potentially bind their structural fragments or functional groups. Such enzymes include cholinesterases, carbonic anhydrase II (CA-II) and cyclin-dependent kinase 2 (CDK-2). A (triazolyl)methyl amide-linked disaccharide nucleoside, based on a new prospective structural framework for analogues of nucleoside diphosphate sugars, was synthesized. The synthetic strategies employed unprotected or partially protected carbohydrate derivatives as precursors, including ribose, glucuronic acid, glucuronolactone, and glycopyranosides and relied on stereoselective N-glycosylation, regioselective Mitsunobu coupling and ‘click chemistry’ approaches. Some 6'-isonucleosides and triazole-containing glycoderivatives displayed moderate selective acetylcholinesterase inhibitory activities. The best inhibitor was an aminomethyltriazole 6'-isonucleoside with a Ki value of 11.9 μM. N-Glucuronylsulfonohydrazide showed good inhibition of CA-II (Ki = 9.5 μM). Molecular docking of the most active compounds into the effected enzymes showed interactions with key amino acid residues for substrate recognition. In addition, the tested compounds did not show toxicity to normal cells.
Keywords: nucleosides; nucleotides; carbohydrates; mimetics; cholinesterases